Production of Cams by a P/M Route. - Vollertsen, Frank; Engel, Ulf (Powder Metallurgy International, 1992)
The production of cams for an integral camshaft by means of powder metallurgical methods is described. The problems of strength, wear resistance, working accuracy (especially carbon control) and production costs are discussed. The choice of an alloy which contians no expensive elements is essential for the reduction of production costs. For wear resistance not only the properties under normal lubrication but also the emergency running properties have to be taken into account.
LFT Import::2019-07-16 (1966)